Tumefactive Fat Necrosis with Multinucleate Giant Cell Reaction Mimicking Recurrent Renal Cell Carcinoma following Percutaneous Renal Cryoablation - Amanda E. Kahn; Kevin J. Wu; David D. Thiel (Case Reports in Urology)
Multinucleate Giant Cell (GC) reaction is a biological response that occurs secondary to infection, an implanted foreign body, tissue injury, or inflammation. In rare instances GC reactions have been reported following tissue ablation. Multinucleate GC reactions and tumefactive fat necrosis both have the ability to mimic cancer recurrence or metastasis and can appear as enhancing masses. We discuss a case of a surgically resected retroperitoneal perinephric mass thought to be recurrent renal cell carcinoma (RCC) that was pathologically confirmed as tumefactive fat necrosis with multinucleate GC reaction 2 years following percutaneous cryoablation of a small renal mass.